Reading Trends of Youth in Pakistan: A Pilot Study - Soroya, Saira Hanif; Ameen, Kanwal (Pakistan Journal of Information Management and Libraries, 2016)
The present study, a part of researcher's Ph.D. project, aimed at exploring the reading trends of young Pakistani students (i.e., Generation Y: born during the 1980s and early 1990s, also known as internet generation), and the impact of digital media on their reading behavior. It was conducted as a pilot study on final year's master level students of the University of the Punjab. Quantitative research design, based on a survey was used. Convenient sampling technique was used to collect data from 50 students through questionnaire survey. It revealed that the students' reading behavior has been significantly changed during the last five years. Their overall reading time and digital reading time has been increased due to the availability of digital devices and digital reading material. The findings of this study are helpful in identifying the trends of reading behavior as well as in planning and designing library services with regard to the considering of the behavior of the students.
Keywords: dept.ils

Anti-fraud schema system for identification and prevention of fraud behaviors in E-commerce services - Yang, Qinghong; Wei, Xing; Hu, Xiangquan; QuanLiu, Yan (Global Journal of Computer Science and Technology, 2016)
Keywords: dept.ils

Multimedia Design & HCI in Libraries - Liu, Dr Yan Quan (2016)
The primary purpose of this book is to help students understand the principles of multimedia interface design to develop essential skills. The underlying philosophy of the approach of this text is that concepts are learned and remembered better when learned in a real work environment.
Keywords: dept.ils

Digital Libraries in Theory and Practices - Liu, Yan Quan (CreateSpace Independent Publishing Platform, 2016)
Keywords: Information storage and retrieval systems; dept.ils; faculty_collection

Effective techniques for the promotion of library services and resources - Yi, Zhixian (Information Research-an International Electronic Journal, 2016)
Introduction. This study examines how Australian academic librarians perceive techniques for promoting services and resources, and the factors affecting the perceptions regarding effectiveness of techniques used. Method. Data were collected from an online survey that was sent to 400 academic librarians in thirty-seven Australian universities. The response rate was 57.5%. Analysis. The qualitative data were analysed using content analysis. The collected quantitative and qualitative data were analysed using descriptive and inferential statistics (ordinal regressions). Results. Librarians used a variety of techniques to promote services and resources. Demographic variables, human capital variables and library variables were significant predictors of perceptions of the effective promotion techniques used. However, this study indicates that other independent variables such as number of different library professional positions and years involved in all library services made no difference. Conclusions. This study provides a better understanding of academic librarians' attitudes and views towards techniques for promoting services and resources. Librarians may use the results to reflect on the effectiveness of these techniques, to balance the weight of the factors' influences and to better understand various promotion techniques. This will enable them to promote library services and resources more effectively in the future.
tex.article-number: 702 tex.unique-id: ISI:000386350500011
Keywords: dept.ils; ⛔ No DOI found

Current market demand for core competencies of librarianship-a text mining study of american library association's advertisements from 2009 through 2014 - Yang, Qinghong; Zhang, Xingzhi; Du, Xiaoping; Bielefield, Arlene; Liu, Yan Quan (Applied Sciences-Basel, 2016)
As librarianship evolves, it is important to examine the changes that have taken place in professional requirements. To provide an understanding of the current market demand for core competencies of librarianship, this article conducts a semi-automatic methodology to analyze job advertisements (ads) posted on the American Library Association (ALA) Joblist from 2009 through 2014. There is evidence that the ability to solve unexpected complex problems and to provide superior customer service gained increasing importance for librarians during those years. The authors contend that the findings in this report question the status quo of core competencies of librarianship in the US job market.
23 citations (Crossref) [2023-10-31] tex.article-number: 48 tex.unique-id: ISI:000371827200001
Keywords: Competency; Job advertisement; Librarianship; Text mining; dept.ils; peer-reviewed